A comparative meta-analysis between chevron and scarf osteotomies in hallux valgus patients - Fahid Alqahtani, Turki (Frontiers in Surgery, 2025)
BackgroundUsually affecting the medial prominence of the first metatarsophalangeal (MTP) joint, hallux valgus is a complicated malformation of the first ray that causes deformed joint structure, dysfunction, and increasing stiffness. The most common methods for treating hallux valgus malformation are scarf osteotomy and chevron osteotomy. Due to the inconsistent and contradictory findings among the studies, we conducted this systematic review and meta-analysis to compare chevron and scarf osteotomies in the management of hallux valgus deformity.MethodsUsing the following search strategy: “Chevron” AND “Scarf” AND “Osteotomy” AND “Hallux Valgus”, and from inception until October 2024, we searched PubMed, Web of Science, and Scopus for relevant publications that needed to be screened to see if they could be included in our study. We performed a meta-analysis of the articles included using Review Manager version 5.4 software, pooling the mean difference (MD) of various outcomes at 95% confidence intervals (CI) and a p-value of 0.05.ResultsChevron osteotomy was observed to lower the hallux valgus angle (HVA) with a significant difference compared with scarf osteotomy, showing a MD = −2.44 (95% CI: −4.57, −0.31, p = 0.03). However, no significant difference was observed between both osteotomies regarding the reduction of intermetatarsal angle (IMA), showing a MD = −0.33 (95% CI: −1.32, 0.66, p = 0.52). Chevron osteotomy was observed to be associated with higher American Orthopedic Foot and Ankle Society (AOFAS) compared with scarf osteotomy with MD = 2.21 (95% CI: 0.7, 3.71, p = 0.004) and I2 = 0%, however, no significant difference was observed regarding their effect on pain with SMD = −0.07 (95% CI: −0.44, 0.31, p = 0.73).ConclusionChevron osteotomy was observed to be superior to scarf osteotomy in lowering the HVA and improving functional outcomes presented by AOFAS measurements. However, they were comparable in their effect on IMA and pain measurements.